Kiat Mengatasi Konflik Antar Karyawan - Lule, Benny (JBE (Journal of Business and Economics); Volume 9 No.2, 2010 JBE UNKLAB, 2010)
Conflict among people in organization happen every day and can arise because of ineffective communication, values and culture clashes, confusing work policies and practices, or adversarial managment. Conflict can have a negative effect on an organization, but if conflict can be resolved appropriately it can have a positive effect by forcing team members toward creative and innovative solutions to the problem. Thre are three main conflict resulation strategies: win/win, win/lose, and lose/lose. Using win/win strategy not only can resolve a conflict but also can preserve relationship. When people cannot solve their conflicts in an informal manner, many organizations create solutions through a conflict resolution process.